East‐Central Asian Climate Evolved With the Northward Migration of the High Proto‐Tibetan Plateau - Chenguang Zhu; Jun Meng; Yongyun Hu; Chengshan Wang; Jian Zhang (Geophysical Research Letters)
Abstract The evolution of Cenozoic climate patterns in Asia has been linked to uplift of the Tibetan Plateau (TP), retreat of the Paratethys Sea, and global cooling. However, less attention has been placed on the latitudinal change of the TP. Here we report new climate modeling to explore how modern climate changes as a function of topographic growth and spatial migration of the TP. Our results show that the northward displacement of the uplifted proto‐TP within the subtropics can significantly affect the wind and precipitation pattern over East‐Central Asia. By compiling proxy‐based climatic records, paleolatitudinal and paleoelevational evolution models of the proto‐TP, and in comparison with previous modeling under a global paleogeography, we suggest that the northward migration of the proto‐TP in the Paleogene could have intensified the aridity in Central Asia, but its influence on East Asian precipitation and monsoonal circulation could be dependent on the paleogeography and other boundary conditions.